Phenomenology of quantum turbulence in superfluid helium - Skrbek, Ladislav; Schmoranzer, David; Midlik, Šimon; Sreenivasan, Katepalli R. (Proceedings of the National Academy of Sciences - PNAS, 2021)
Quantum turbulence—the stochastic motion of quantum fluids such as ⁴He and ³He-B, which display pure superfluidity at zero temperature and two-fluid behavior at finite but low temperatures—has been a subject of intense experimental, theoretical, and numerical studies over the last half a century. Yet, there does not exist a satisfactory phenomenological framework that captures the rich variety of experimental observations, physical properties, and characteristic features, at the same level of detail as incompressible turbulence in conventional viscous fluids. Here we present such a phenomenology that captures in simple terms many known features and regimes of quantum turbulence, in both the limit of zero temperature and the temperature range of two-fluid behavior.